Phenomenology Study: The Experiences of Nurses in Community To Involving Parents, Teen, And Peers To Prevention Free Sex Among Teenagers - Mulyadi, Budhi; Agung Waluyo; Dewi Irawati; Ede Surya Darmawan (Caring: Indonesian Journal of Nursing Science, 2019)
WHO reported that 30-50% of teenagers pregnance have until 19 year old in the world (2011) .in Indonesia, Teenagers having sex in Bandung, 54%, 51% Jakarta, and Surabaya 47% (JPNN, 2014). Campaign for teenagers condom use not accordance with Indonesian culture. Indonesia is not justified HIV prevention and teen pregnancy with condom use campaign. Phenomenological study method by in-depth interview nurses in the community about the experience of involving parents, teens, and peers to prevent free sex in adolescents. The result is that in order to prevent free sex in adolescents should involve parents, teens, and peers.